Quantifying positive communication: Doctor's language and patient anxiety in primary care consultations. Issue 9 (September 2018) - Stortenbeker, Inge A.; Houwen, Juul; Lucassen, Peter L.B.J.; Stappers, Hugo W.; Assendelft, Willem J.J.; van Dulmen, Sandra; olde Hartman, Tim C.; Das, Enny
Highlights: This study systematically disentangles content from message directness in messages of GPs. GPs express more direct positive and indirect negative messages in communication with patients with MES but not MUS. The use of direct negative messages is related to an increase in patient anxiety. Abstract: Objective: Positive communication is advocated for physicians during consultations with patients presenting medically unexplained symptoms (MUS), but studies generally focus on what is said rather than how it is said. This study quantified language use differences of general practitioners (GPs), and assessed their relation to patient anxiety. Methods: Language use of 18 Dutch GPs during 82 consultations was compared for patients with MUS versus medically explained symptoms (MES). Message content (positive or negative) was differentiated from its directness (direct or indirect), and related to changes in patient's state anxiety (abbreviated State Trait Anxiety Inventory; STAI). Results: In total, 2590 clauses were identified. GPs approached patients with MES with relatively more direct (vs. indirect) positive and indirect (vs. direct) negative messages (OR 1.91, 95% CI 1.42–2.59). Anxiety of both patient groups increased when GPs used more direct (vs. indirect) negative messages ( b ?=?0.67, 95% CI 0.07–1.27) Conclusions: GPs use different language depending on the content of messages for patients with MES, but not MUS. Direct negative messages relate to an increase in patient anxiety. Practice implications: GPs could manage patient's state anxiety by expressing negative messages in an indirect rather than direct manner.